Comunidad de roedores en el municipio de San Marcos, Sucre, Colombia - Blanco, T. Pedro; Corrales, A. Homer; Arroyo, M. Steven; Pérez, J. Julia; Álvarez, G. Lercy; Castellar, M. Anaís (Universidad de Sucre: Facultad de Ciencias Agropecuarias, 2012)
The aim of this research was to determinate the composition of rodent communities in urban and rural areas from San Marcos, Sucre, Colombia. Rodents were sampled using Sherman traps from December 2007 to July 2009, with a capture effort of 1200 night traps (capture success 12%). A total of 144 rodents were captured, eight species were registered: Mus musculus (60), Zygodontomys brevicauda (44), Rattus rattus (21), Oryzomys azuerensis (10), Oligoryzomys fulvescens (4), Neacomys spinosus (2), Proechiymys cayennensis (2), and Heteromys anomalus (1). The number of murinae rodents was higher in urban habitats, whereas wild rodent species of subfamily Sigmodontinae were dominant in rural areas. In addition, the highest percentage of population consisted of adult males. Data suggest that characteristics of habitats (homogeneity and heterogeneity) were important factors on species distribution and diversity of rodents in both urban and rural area. El objetivo de esta investigación fue determinar la composición de las comunidades de roedores en áreas urbanas y rurales del municipio de San Marcos, Sucre, Colombia. Los roedores fueron muestreados empleando trampas tipo Sherman desde diciembre de 2007 hasta julio de 2009, con un esfuerzo de captura de 1200 trampas-noche (éxito de captura 12%). Fueron capturados un total de 144 individuos, registrándose 8 especies: Mus musculus (60), Zygodontomys brevicauda (44), Rattus rattus (21), Oryzomys azuerensis (10), Oligoryzomys fulvescens (4), Neacomys spinosus (2), Proechiymys cayennensis (2) y Heteromys anomalus (1). El número de roedores murinos fue mayor en hábitats urbanos, mientras en ambientes rurales predominaron las especies silvestres de la subfamilia Sigmodontinae. Además, el mayor porcentaje de la población correspondió a machos adultos. Los resultados sugieren que las condiciones (homogeneidad y heterogeneidad) de los hábitats fueron determinantes en la distribución y diversidad de los roedores tanto en ambientes urbanos como rurales.